Negative electrode for secondary battery, secondary battery, and method for producing negative electrode for secondary battery

By designing a negative electrode mixture layer containing carbon material and Si-based materials in the negative electrode of the secondary battery, and controlling the pore size distribution and adhesive content, the problem of negative electrode expansion is solved, and higher battery capacity and stability are achieved.

CN119731797APending Publication Date: 2025-03-28PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380060423.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-29
Filing Date
2023-08-02
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The high capacity of Si-based materials in secondary batteries has been achieved, but the expansion of the negative electrode has become a problem and it is necessary to suppress expansion.

Method used

The negative electrode current collector and the negative electrode mixture layer were used, which contained a negative electrode active material of carbon material and a Si-based material, and the adhesive agent was determined to have two peaks R1 and R2 by mercury pressing method, and the adhesive content was 4 mass % or more.

Benefits of technology

It effectively suppresses the expansion of the negative electrode, improves the permeability of the electrolyte, and enhances the capacity and stability of the secondary battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005275226140000131
    Figure BDA0005275226140000131
  • Figure HDA0005275226150000011
    Figure HDA0005275226150000011
Patent Text Reader

Abstract

A negative electrode for a secondary battery according to one embodiment of the present disclosure is provided with a negative electrode current collector and a negative electrode mixture layer disposed on the negative electrode current collector, and is characterized in that the negative electrode mixture layer comprises a binder and a negative electrode active material containing a carbon material and an Si-based material, the negative electrode active material is characterized in that the pore diameter distribution of the negative electrode mixture layer has two peak values R1 and R2 as measured by mercury intrusion method, the peak value R1 is 0.5 [mu] m to 1.5 [mu] m inclusive, the peak value R2 is 2 [mu] m to 10 [mu] m inclusive, and the content of the binder contained in the negative electrode mixture layer is 4 mass% or more with respect to the total mass of the negative electrode active material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a negative electrode for a secondary battery, a secondary battery, and a method for producing the negative electrode for a secondary battery. Background Art

[0002] As a material that can achieve high capacity of batteries, Si-based materials are currently attracting attention. Si-based materials are materials that can electrochemically store and release lithium ions, and can be charged and discharged at a much larger capacity than carbon materials such as graphite.

[0003] For example, Patent Document 1 discloses a negative electrode active material for a lithium ion secondary battery, which contains a Si-based material represented by SiOx (0<x<2) and a carbon material, and is characterized in that the negative electrode active material for a lithium ion secondary battery has voids inside.

[0004] In addition, for example, Patent Document 2 discloses a method for manufacturing a negative electrode for a lithium ion secondary battery, wherein the negative electrode for a lithium ion secondary battery has a collector and a negative electrode active material layer stacked on the collector, the negative electrode active material layer having a silicon oxide (Si-based material) represented by SiOx (0.3≤x≤1.6), and a conductor in the form of particles containing a metal element, wherein a surface portion of the negative electrode active material layer located on the opposite side of the collector contains more of the conductor than an inner portion of the negative electrode active material layer located on the collector side, and the manufacturing method The method is characterized in that it comprises a preparation step, a heating step and a removal step. In the preparation step, a negative electrode intermediate having the collector, a negative electrode mixture layer and a metal layer is prepared, the negative electrode mixture layer having an acidic resin and a silicon oxide represented by SiOx (0.3≤x≤1.6) and being stacked on the collector, and the metal layer containing the metal element and being stacked on the upper layer of the negative electrode mixture layer. In the heating step, the negative electrode intermediate is heated to a temperature at which at least a portion of the acidic resin is decomposed. In the removal step, the metal layer is removed after the heating step.

[0005] Prior Art Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2013-219059

[0007] Patent Document 2: Japanese Patent No. 5691867 Summary of the invention

[0008] However, although Si-based materials can realize a high capacity of secondary batteries, swelling of the negative electrode becomes a problem and improvement is desired.

[0009] Therefore, an object of the present disclosure is to provide a negative electrode for a secondary battery, a secondary battery, and a method for producing a negative electrode for a secondary battery, which can suppress swelling of the negative electrode.

[0010] A technical solution disclosed herein relates to a negative electrode for a secondary battery, characterized in that it comprises a negative electrode collector and a negative electrode mixture layer arranged on the negative electrode collector, the negative electrode mixture layer comprises a negative electrode active material comprising a carbon material and a Si-based material, and a binder, the pore size distribution of the negative electrode mixture layer measured by mercury penetration has two peaks R1 and R2, the peak R1 is greater than 0.5 μm and less than 1.5 μm, and the peak R2 is greater than 2 μm and less than 10 μm, and the content of the binder contained in the negative electrode mixture layer is greater than 4 mass % relative to the total mass of the negative electrode active material.

[0011] A secondary battery according to one aspect of the present disclosure is characterized by comprising the secondary battery negative electrode.

[0012] A technical solution disclosed herein relates to a method for manufacturing a negative electrode for a secondary battery, characterized in that the method comprises a first step and a second step, wherein in the first step, a negative electrode paste containing a negative electrode active material, a binder and a pore-forming material is applied to a negative electrode collector to form a coating film, and then the coating film is rolled, wherein the negative electrode active material contains a carbon material and a Si-based material, and in the second step, after the first step, the coating film is heat-treated to decompose and gasify the pore-forming material to form a negative electrode mixture layer, wherein the pore size distribution of the negative electrode mixture layer measured by mercury penetration has two peaks R1 and R2, wherein the peak R1 is greater than 0.5 μm and less than 1.5 μm, and the peak R2 is greater than 2 μm and less than 10 μm, and the content of the binder contained in the negative electrode mixture layer is greater than 4% by mass relative to the total mass of the negative electrode active material.

[0013] According to the present disclosure, it is possible to provide a negative electrode for a secondary battery, which can suppress swelling of the negative electrode, a secondary battery, and a method for producing the negative electrode for a secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 It is a cross-sectional view of a secondary battery according to an example of an embodiment. DETAILED DESCRIPTION

[0015] A negative electrode for a secondary battery according to an embodiment of the present disclosure comprises a negative electrode collector and a negative electrode mixture layer disposed on the negative electrode collector, wherein the negative electrode mixture layer comprises a negative electrode active material including a carbon material and a Si-based material and a binder, wherein the pore size distribution of the negative electrode mixture layer measured by mercury penetration has two peaks R1 and R2, wherein the peak R1 is greater than 0.5 μm and less than 1.5 μm, and the peak R2 is greater than 2 μm and less than 10 μm, and the content of the binder contained in the negative electrode mixture layer is greater than 4% by mass relative to the total mass of the negative electrode active material. As in the present disclosure, the negative electrode mixture layer having two peaks (R1, R2) in the pore size distribution that meet the above range is presumed to suppress the expansion of the negative electrode due to the formation of voids that are most suitable for absorbing the expansion and contraction of the Si-based material accompanying charge and discharge. In addition, it is presumed that by making the content of the binder meet the above range, the amount of the binder attached to the Si-based material can be sufficiently ensured, so that the expansion of the negative electrode is further suppressed. As described later, when manufacturing the negative electrode for the secondary battery of the present disclosure, a pore-forming material is used, but since the binder also adheres to the pore-forming material, if the content of the binder is small, it is difficult to ensure a sufficient amount of the binder adhered to the Si-based material. In addition, the pore-forming material is decomposed and gasified and disappears by the heat treatment during the manufacture of the negative electrode, so it is estimated that the binder adhered to the pore-forming material is isolated and is in a state where it hardly works on suppressing the swelling of the negative electrode.

[0016] Hereinafter, embodiments of the negative electrode active material for a secondary battery and the secondary battery according to the present disclosure will be described in detail with reference to the drawings.

[0017] Hereinafter, an example of a secondary battery according to one aspect of the present disclosure will be described.

[0018] Figure 1 It is a cross-sectional view of a secondary battery according to an example of an embodiment. Figure 1 The secondary battery 10 shown in the figure comprises: a wound electrode body 14 in which a positive electrode 11 and a negative electrode 12 are wound with a separator 13 interposed therebetween, a non-aqueous electrolyte, insulating plates 18 and 19 respectively arranged above and below the electrode body 14, and a battery case 15 for accommodating the above components. The battery case 15 is composed of a case body 16 in a cylindrical shape with a bottom and a sealing body 17 that seals the opening of the case body 16. In addition, instead of the wound electrode body 14, an electrode body in other forms such as a laminated electrode body in which a positive electrode and a negative electrode are alternately laminated with a separator interposed therebetween may be applied. In addition, as the battery case 15, a metal case in a cylindrical, square, coin-shaped, button-shaped, etc., a resin case formed by laminating resin sheets (so-called laminated type), etc. may be exemplified.

[0019] The nonaqueous electrolyte is, for example, an electrolyte having lithium ion conductivity, and may be a liquid electrolyte (electrolyte) or a solid electrolyte.

[0020] The liquid electrolyte (electrolyte) includes, for example, a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. As disclosed herein, the two peaks (R1, R2) in the pore size distribution satisfy the negative electrode mixture layer within the above range. It is inferred that the expansion of the negative electrode can be further suppressed by using an electrolyte because a gap that is most suitable for improving the permeability of the electrolyte is formed. Non-aqueous solvents may include, for example, esters, ethers, nitriles, amides, and mixed solvents of two or more thereof. As an example of a non-aqueous solvent, ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and mixed solvents thereof may be cited. The non-aqueous solvent may also contain a halogen substitute (e.g., fluoroethylene carbonate, etc.) in which at least a portion of the hydrogen of these solvents is replaced by a halogen atom such as fluorine. The electrolyte salt may include, for example, a lithium salt such as LiPF6.

[0021] In addition, as a solid electrolyte, for example, a solid or gel-like polymer electrolyte, an inorganic solid electrolyte, etc. can be used. As an inorganic solid electrolyte, well-known materials in all-solid lithium-ion secondary batteries, etc. (such as oxide-based solid electrolytes, sulfide-based solid electrolytes, halogen-based solid electrolytes, etc.) can be used. The polymer electrolyte, for example, contains a lithium salt and a matrix polymer, or contains a non-aqueous solvent, a lithium salt and a matrix polymer. As a matrix polymer, for example, a polymer material that absorbs a non-aqueous solvent and gels can be used. As a polymer material, fluororesins, acrylic resins, polyether resins, etc. can be cited. In addition, the non-aqueous electrolyte is just an example, and an aqueous electrolyte can also be used as long as it is applicable.

[0022] The case body 16 is, for example, a metal container in a cylindrical shape with a bottom. A gasket 28 is provided between the case body 16 and the sealing body 17 to ensure the airtightness of the battery interior. The case body 16 has, for example, an extension portion 22 in which a part of the side surface extends inward and supports the sealing body 17. The extension portion 22 is preferably formed in an annular shape along the circumferential direction of the case body 16, and supports the sealing body 17 on its upper surface.

[0023] The sealing body 17 has a structure in which a filter 23, a lower valve body 24, an insulating component 25, an upper valve body 26 and a cover 27 are stacked in order from the electrode body 14 side. The components constituting the sealing body 17 have, for example, a disc shape or a ring shape, and the components except the insulating component 25 are electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected to each other at their respective central portions, and an insulating component 25 is sandwiched between their respective peripheral portions. When the internal pressure of the secondary battery 10 rises due to heat caused by an internal short circuit, for example, the lower valve body 24 is deformed and ruptured in a manner that pushes the upper valve body 26 toward the cover 27 side, and the current path between the lower valve body 24 and the upper valve body 26 is cut off. When the internal pressure rises further, the upper valve body 26 ruptures, and the gas is discharged from the opening of the cover 27.

[0024] exist Figure 1 In the secondary battery 10 shown, the positive electrode lead 20 installed on the positive electrode 11 extends to the sealing body 17 side through the through hole of the insulating plate 18, and the negative electrode lead 21 installed on the negative electrode 12 extends to the bottom side of the case body 16 through the outside of the insulating plate 19. The positive electrode lead 20 is connected to the bottom plate of the sealing body 17, that is, the lower surface of the filter 23, by welding or the like, and the top plate of the sealing body 17, that is, the cover 27 electrically connected to the filter 23 becomes the positive terminal. The negative electrode lead 21 is connected to the bottom inner surface of the case body 16 by welding or the like, and the case body 16 becomes the negative terminal.

[0025] Hereinafter, the positive electrode 11 , the negative electrode 12 , and the separator 13 will be described in detail.

[0026] [positive electrode]

[0027] The positive electrode 11 has a positive electrode current collector and a positive electrode mixture layer arranged on the positive electrode current collector. The positive electrode current collector can use a foil of a metal such as aluminum that is stable within the potential range of the positive electrode 11, a thin film having the metal arranged on the surface, and the like. The positive electrode mixture layer is composed of, for example, a positive electrode active material, a binder, a conductive material, and the like. The positive electrode 11 can be made, for example, as follows: a positive electrode paste containing a positive electrode active material, a binder, and a conductive material is applied to the surface of the positive electrode current collector, and after the coating is dried, it is rolled to form a positive electrode mixture layer on both sides of the positive electrode current collector.

[0028] As the conductive material contained in the positive electrode mixture layer, carbon materials such as carbon black, acetylene black, Ketjen black, graphite, and carbon nanotubes can be exemplified. As the binder contained in the positive electrode mixture layer, fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide resins, acrylic resins, polyolefin resins, styrene-butadiene rubber (SBR), cellulose derivatives of carboxymethyl cellulose (CMC) or its salts, polyacrylic acid (PAA) or its salts, polyethylene oxide (PEO), polyvinyl alcohol (PVA), etc. can be cited.

[0029] As the positive electrode active material, for example, lithium transition metal composite oxides can be used. As the metal elements contained in the lithium transition metal composite oxide, Ni, Co, Mn, Al, B, Mg, Ti, V, Cr, Fe, Cu, Zn, Ga, Sr, Zr, Nb, In, Sn, Ta, W, etc. can be cited. Among them, it is preferred to contain at least one of Ni, Co, and Mn. As an example of a preferred lithium transition metal composite oxide, a composite oxide represented by the general formula LiMO2 (M is Ni and X, X is a metal element other than Ni, and the proportion of Ni is 50 mol% or more and 95 mol% or less relative to the total molar number of metal elements other than Li) can be cited. X in the above formula can, for example, include Co, Mn, Al, B, Mg, Ti, V, Cr, Fe, Cu, Zn, Ga, Sr, Zr, Nb, In, Sn, Ta, W, etc.

[0030] [negative electrode]

[0031] The negative electrode 12 has a negative electrode current collector and a negative electrode mixture layer arranged on the negative electrode current collector. The negative electrode current collector can use a foil of a metal such as copper that is stable within the potential range of the negative electrode 12, a thin film of the metal arranged on the surface, etc. The negative electrode mixture layer contains a negative electrode active material and a binder, and may also contain a conductive material, etc. The negative electrode active material contains a carbon material and a Si-based material. In addition to the carbon material or the Si-based material, the negative electrode active material may also contain a substance that can reversibly absorb and release lithium ions. The conductive material can include the same materials as those in the case of the positive electrode 11.

[0032] The pore size distribution of the negative electrode mixture layer measured by mercury intrusion porosimetry has two peaks R1 and R2. The peak R1 is 0.5 μm or more and 1.5 μm or less, and the peak R2 is 2 μm or more and 10 μm or less.

[0033] In the mercury intrusion method, mercury is pressurized to penetrate into the pores of a solid sample, and the diameter and volume (capacity) of the pores are calculated based on the pressure applied to the mercury and the amount of mercury pressed into the pores. When mercury with a pressure P applied can penetrate into a pore of diameter D, the diameter D of the pore is calculated from the pressure P, the contact angle θ of mercury, and the surface tension σ of mercury according to the following formula. In addition, the pore volume is calculated from the amount of mercury pressed into the pores. In addition, in the present disclosure, the pore diameter refers to the diameter of the pore.

[0034] -4σcosθ=PD

[0035] The pore size distribution measured by mercury intrusion porosimetry is obtained by plotting the Log differential pore volume (cm2) against the average pore size (μm) of each measurement site. 3 / g), the horizontal axis is the pore diameter (μm), the vertical axis is the Log differential pore volume (cm 3 Here, in the present disclosure, the peak value in the pore size distribution refers to the pore size at the top of the peak in the pore size distribution.

[0036] The peak value R1 may be greater than 0.5 μm and less than 1.5 μm, for example, preferably greater than 0.8 μm and less than 1.2 μm. If the peak value R1 is less than 0.5 μm, there are many small gaps between the particles in the negative electrode mixture layer, so that, for example, the permeability of the electrolyte is reduced, and the high capacity of the secondary battery cannot be achieved. In addition, if the peak value R1 exceeds 1.5 μm (less than 2 μm), for example, the density of the negative electrode active material is reduced, and the high capacity of the secondary battery cannot be achieved. In addition, the peak value R2 may be greater than 2 μm and less than 10 μm, for example, preferably greater than 4 μm and less than 8 μm. If the peak value R2 is less than 2 μm, for example, there are few gaps in the negative electrode mixture layer that can absorb the expansion and contraction of the Si-based material accompanying charging and discharging, so the expansion of the negative electrode cannot be suppressed. In addition, if the peak value R2 is greater than 10 μm, for example, there are many large gaps in the negative electrode mixture layer, so the density of the negative electrode active material is reduced, and the high capacity of the secondary battery cannot be achieved.

[0037] The measurement of pore size distribution by mercury intrusion is performed on the negative electrode mixture layer before initial charging. For example, a measurement sample obtained by punching a negative electrode for a secondary battery into a predetermined shape before initial charging can be used, and the pore size distribution of the negative electrode mixture layer of the measurement sample can be measured by mercury intrusion. In addition, the measurement sample only needs to have a negative electrode mixture layer on the surface, and may also have other structures such as a negative electrode collector.

[0038] The measurement of pore size distribution by mercury intrusion method can be carried out, for example, using an apparatus such as the AutoPore IV 9500 series manufactured by Micromeritics. During the measurement, the sample for measurement is sealed in a sample container under an inert atmosphere, and mercury is injected into the sample container to apply pressure to the mercury. Here, the pressure applied to the mercury is appropriately adjusted according to the size of the pore size that the sample for measurement can have, and there is no particular limitation. For example, the pressure can be changed from 0.5 psi (3.4 kPa) to 60000 psi (413400 kPa) for measurement, which is preferred from the viewpoint of being able to measure the pore size over a wide range.

[0039] The Si-based material contained in the negative electrode active material is not particularly limited as long as it is a material that can reversibly absorb and release lithium ions, and examples thereof include Si particles, alloy particles containing Si, and Si compound particles, etc. These can be used alone or in combination of two or more.

[0040] Si particles can be obtained by a gas phase method or by finely grinding silicon chips, and Si particles manufactured by any method can also be used. Examples of Si-containing alloy particles include alloys containing Si and a metal selected from alkali metals, alkaline earth metals, transition metals, rare earth metals, or a combination thereof. Examples of Si compound particles include Si compound particles having a silicate phase and Si particles dispersed in the silicate phase, Si compound particles having a silicon oxide phase and Si particles dispersed in the silicon oxide phase, and Si compound particles having a carbon phase and Si particles dispersed in the carbon phase. Among them, from the perspective of increasing the capacity of the secondary battery or suppressing the reduction in charge and discharge cycle characteristics, Si compound particles having a silicate phase and Si particles dispersed in the silicate phase or Si compound particles having a carbon phase and Si particles dispersed in the carbon phase are preferred.

[0041] As the silicate phase, for example, from the viewpoint of high lithium ion conductivity, it is preferred to contain at least one element selected from lithium, sodium, potassium, rubidium, cesium, dysprosium, beryllium, magnesium, calcium, strontium, barium, and radium. Among them, from the viewpoint of high lithium ion conductivity, the silicate phase is preferably a silicate phase containing lithium (hereinafter sometimes referred to as a lithium silicate phase).

[0042] The lithium silicate phase is represented by the formula: Li 2z SiO 2+z (0<z<2). From the viewpoints of stability, ease of production, lithium ion conductivity, etc., z preferably satisfies the relationship of 0<z<1, and more preferably z=1 / 2.

[0043] The Si compound particles having Si particles dispersed in the silicon oxide phase can be represented by the general formula SiOx (preferably in the range of 0<x<2, and more preferably in the range of 0.5≤x≤1.6). The Si compound particles having Si particles dispersed in the carbon phase can be represented by the general formula SixC1y (preferably in the range of 0<x≤1 and 0<y≤1, and more preferably in the range of 0.3≤x≤0.45 and 0.7≤y≤0.55).

[0044] It is preferred to form a conductive film composed of a material with high conductivity on the particle surface of the Si-based material. As the conductive film, carbon film, metal film and metal compound film can be cited. From the perspective of electrochemical stability, carbon film is preferred. The carbon film can be formed, for example, by a CVD method using acetylene, methane, etc., by mixing coal tar, petroleum asphalt, phenolic resin, etc. with a silicon-based active material and performing a heat treatment. In addition, a conductive film can also be formed by fixing a conductive filler such as carbon black on the particle surface of the Si-based material using an adhesive.

[0045] The content of the Si-based material is preferably 30% by mass or more relative to the total mass of the negative electrode active material, for example, from the viewpoint of increasing the capacity of the secondary battery. In addition, from the viewpoint of achieving a high capacity of the secondary battery and further suppressing the swelling of the negative electrode, the content of the Si-based material is preferably 30% by mass or more and 60% by mass or less, and more preferably 35% by mass or more and 55% by mass or less relative to the total mass of the negative electrode active material.

[0046] For example, from the perspective of suppressing the reduction of charge-discharge cycle characteristics caused by side reactions with non-aqueous electrolytes, the average particle size of the Si-based material is preferably 4 μm or more. In addition, from the perspective of suppressing the reduction of charge-discharge cycle characteristics and further suppressing the expansion of the negative electrode, the average particle size of the Si-based material is preferably, for example, 4 μm or more and 12 μm or less, and more preferably 6 μm or more and 10 μm or less.

[0047] The carbon material contained in the negative electrode active material may be, for example, a carbon material known in the past for use as a negative electrode active material for a secondary battery. From the perspective of further suppressing the reduction in charge and discharge cycle characteristics, preferred graphites include natural graphites such as flaky graphite, blocky graphite, and earthy graphite, and artificial graphites such as blocky artificial graphite (MAG) and graphitized mesophase carbon microbeads (MCMB).

[0048] For example, from the viewpoint of further suppressing the swelling of the negative electrode, the average particle size of the carbon material is preferably 10 μm or more and 25 μm or less, and more preferably 12 μm or more and 20 μm or less.

[0049] The average particle size of each material is a volume average particle size D50 at a volume cumulative value of 50% in a particle size distribution obtained by a laser diffraction scattering method.

[0050] The content of the carbon material is, for example, preferably 40% by mass or more and 70% by mass or less, and more preferably 45% by mass or more and 65% by mass or less, based on the total mass of the negative electrode active material.

[0051] As the binder contained in the negative electrode mixture layer, as with the positive electrode 11, fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide resins, acrylic resins, polyolefin resins, styrene-butadiene rubber (SBR), cellulose derivatives of carboxymethyl cellulose (CMC) or its salts, polyacrylic acid (PAA) or its salts, polyethylene oxide (PEO), polyvinyl alcohol (PVA), etc. can be cited. Among them, from the viewpoint of further suppressing the expansion of the negative electrode, the binder preferably contains at least one selected from styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC) or its salts, polyacrylic acid (PAA) or its salts.

[0052] From the viewpoint of suppressing the expansion of the negative electrode, the content of the binder relative to the total mass of the negative electrode active material can be 4% by mass or more, preferably 6% by mass or more, and more preferably 8% by mass or more. The upper limit of the content of the binder, for example, from the viewpoint of the energy density of the battery, relative to the total mass of the negative electrode active material, can be 20% by mass or less, or can be 15% by mass or less.

[0053] An example of a method for manufacturing the negative electrode 12 is described. The negative electrode 12 has a first step and a second step. In the first step, a negative electrode paste containing a negative electrode active material, a pore-forming material, and a binder is applied to a negative electrode current collector to form a coating film, and then the coating film is rolled. The negative electrode active material contains a carbon material and a Si-based material. In the second step, after the first step, the coating film is heated to decompose and gasify the pore-forming material to form a negative electrode mixture layer.

[0054] By heat-treating the coating, the pore-forming material is decomposed and vaporized (for example, sublimated), and the pore-forming material is separated from the coating, thereby forming not only small gaps but also larger gaps between the particles in the negative electrode mixture layer. In this way, by heat-treating the negative electrode paste to which the pore-forming material is added, the pore distribution of the negative electrode mixture layer has a peak R1 of more than 0.5 μm and less than 1.5 μm and a peak R2 of more than 2 μm and less than 10 μm. On the other hand, if a negative electrode paste that does not contain a pore-forming material is used, only small gaps are formed between the particles in the resulting negative electrode mixture layer. Therefore, in the case of using a negative electrode paste to which a pore-forming material is not added, the pore distribution of the negative electrode mixture layer usually only has a peak R1 of more than 0.5 μm and less than 1.5 μm.

[0055] From the viewpoint of suppressing the expansion of the negative electrode, the content of the binder contained in the negative electrode paste may be 4% by mass or more, preferably 6% by mass or more, and more preferably 8% by mass or more relative to the total mass of the negative electrode active material. The upper limit of the content of the binder contained in the negative electrode paste may be, for example, 20% by mass or less, or 15% by mass or less.

[0056] The heat treatment temperature is not particularly limited as long as it is a temperature at which the pore-forming material decomposes and vaporizes. The heat treatment time may be sufficient to ensure a time sufficient for the pore-forming material in the coating film to decompose and vaporize, and may be, for example, 5 hours or more.

[0057] As the pore-forming material, a known pore-forming material can be used. As the pore-forming material, for example, metal oxalates, camphor, naphthalene, etc. can be cited. In addition, as the pore-forming material, for example, dicarboxylic acids such as fumaric acid, malonic acid, and malic acid can also be used. The average particle size of the pore-forming material is, for example, preferably greater than 2 μm and less than 10 μm. By making the average particle size of the pore-forming material within the above range, the peak R2 in the pore size distribution of the negative electrode mixture layer can be easily controlled within the range of greater than 2 μm and less than 10 μm. In addition, in the case of using a pore-forming material with an average particle size outside the above range, the peaks R2 and R1 in the pore size distribution of the negative electrode mixture layer can be controlled by adjusting the viscosity of the negative electrode paste by using the average particle size of each material used in the negative electrode active material, adding a solvent, etc., adjusting the heating treatment time and temperature, adjusting the linear pressure during film rolling, etc.

[0058] The negative electrode active material, pore-forming material, adhesive and other raw materials are mixed when obtaining the negative electrode paste. For example, a cutting mill, a pin mill, a bead mill, a microparticle compounding device (a device that generates shear force between a rotor with a special shape rotating at high speed inside a tank and a collision plate), a granulator, a twin-shaft extruder mixer or a mixer such as a planetary mixer can be used.

[0059] The negative electrode paste can be applied using, for example, a slot die coater, a reverse roll coater, a lip coater, a blade coater, a knife coater, a gravure coater, a dip coater, or the like.

[0060] When the negative electrode paste is applied to the negative electrode current collector to obtain a coating film, the coating film is preferably dried by heating. The heating and drying temperature is preferably a temperature at which the pore-forming material does not decompose or vaporize, but the heating and drying may partially decompose or vaporize the pore-forming material.

[0061] The coating film can be rolled several times at a predetermined linear pressure using, for example, a roll press until the coating film reaches a predetermined thickness.

[0062] [Diaphragm]

[0063] The separator 13 uses, for example, a porous sheet having ion permeability and insulation. Specific examples of the porous sheet include microporous films, woven fabrics, nonwoven fabrics, etc. The material of the separator 13 is preferably polyolefins such as polyethylene and polypropylene, cellulose, etc. The separator 13 may be a single-layer structure or a laminated structure. A heat-resistant layer may be formed on the surface of the separator.

[0064] Example 1

[0065] Hereinafter, the present disclosure will be further described by way of examples, but the present disclosure is not limited to these examples.

[0066] <Example 1>

[0067] [Production of negative electrode]

[0068] Graphite particles with an average particle size of 17 μm and Si-based materials with an average particle size of 8 μm in which Si particles are dispersed in the carbon phase are mixed in a mass ratio of 50:50. The mixture is used as a negative electrode active material. Then, 100 parts by mass of the negative electrode active material, 2 parts by mass of carboxymethyl cellulose (CMC) as a binder, 2 parts by mass of styrene-butadiene rubber (SBR) as a binder, 1 part by mass of multilayer carbon nanotubes, and 12.5 parts by mass of fumaric acid (average particle size 6 μm) are mixed, and mixed with any water to prepare a negative electrode paste. The negative electrode paste is applied to both sides of a negative electrode collector composed of copper foil, and after the coating is dried, the coating is rolled using a calendering roller. Then, the coating is heat-treated at 200°C for 5 hours, thereby preparing a negative electrode having a negative electrode mixture layer formed on both sides of the negative electrode collector.

[0069] The pore size distribution of the negative electrode mixture layer of the obtained negative electrode was measured by mercury penetration. The result showed two peaks, R1 and R2. The peak R1 was 1 μm, and the peak R2 was 6 μm.

[0070] [Production of positive electrode]

[0071] 98 parts by mass of LiCo 1 / 3 Mn 1 / 3 Ni 1 / 3 A lithium transition metal composite oxide represented by O2, 1 part by mass of acetylene black, and 1 part by mass of polyvinylidene fluoride as a binder are mixed, and N-methyl-2-pyrrolidone (NMP) is added to prepare a positive electrode paste. The negative electrode paste is applied to both sides of an aluminum foil, and after the coating is dried, the coating is rolled using a calendering roll to prepare a positive electrode having a positive electrode mixture layer formed on both sides of a positive electrode collector.

[0072] [Preparation of non-aqueous electrolyte]

[0073] In a mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a mass ratio of 1:3, LiPF6 was dissolved at a concentration of 1 mol / L to prepare a non-aqueous electrolyte.

[0074] [Production of test unit]

[0075] The positive electrode and the negative electrode are stacked in a mutually opposed manner with a polyolefin separator interposed therebetween, and the electrode body is wound to produce the electrode body. Next, the electrode body is housed in a bottomed cylindrical battery case body, the non-aqueous electrolyte is injected, and the opening of the battery case body is sealed with a gasket and a sealing body to produce a test unit.

[0076] <Example 2>

[0077] In the preparation of the negative electrode, the test unit was prepared in the same manner as in Example 1, except that carboxymethyl cellulose (CMC) was set to 4 parts by mass and styrene-butadiene rubber (SBR) was set to 4 parts by mass. In the negative electrode of Example 2, the pore size distribution of the negative electrode mixture layer was measured by mercury intrusion porosimetry, and the results showed two peaks R1 and R2, with the peak R1 being 1 μm and the peak R2 being 6 μm.

[0078] <Example 3>

[0079] In the preparation of the negative electrode, the test unit was prepared in the same manner as in Example 1, except that carboxymethyl cellulose (CMC) was set to 5 parts by mass and styrene-butadiene rubber (SBR) was set to 5 parts by mass. In the negative electrode of Example 3, the pore size distribution of the negative electrode mixture layer was measured by mercury intrusion porosimetry, and the results showed two peaks R1 and R2, with the peak R1 being 1 μm and the peak R2 being 6 μm.

[0080] <Comparative Example 1>

[0081] In the preparation of the negative electrode, the test unit was prepared in the same manner as in Example 1, except that the carboxymethyl cellulose (CMC) was set to 1.5 parts by mass and the styrene-butadiene rubber (SBR) was set to 1.5 parts by mass. In the negative electrode of Comparative Example 1, the pore size distribution of the negative electrode mixture layer was measured by mercury intrusion porosimetry, and the results showed two peaks R1 and R2, with the peak R1 being 1 μm and the peak R2 being 6 μm.

[0082] <Comparative Example 2>

[0083] In the preparation of the negative electrode, the test unit was prepared in the same manner as in Example 1, except that the carboxymethyl cellulose (CMC) was set to 0.5 parts by mass and the styrene-butadiene rubber (SBR) was set to 0.5 parts by mass. In the negative electrode of Comparative Example 2, the pore size distribution of the negative electrode mixture layer was measured by mercury intrusion porosimetry, and the results showed two peaks R1 and R2, with the peak R1 being 1 μm and the peak R2 being 6 μm.

[0084] <Comparative Example 3>

[0085] The negative electrode was prepared in the same manner as in Example 1 except that fumaric acid having an average particle size of 1 μm was used. In the negative electrode of Comparative Example 3, the pore size distribution of the negative electrode mixture layer was measured by mercury intrusion porosimetry and showed one peak R1 at 1 μm.

[0086] [Evaluation of negative electrode expansion rate]

[0087] The test unit of each embodiment and each comparative example was charged at a constant current of 1 / 3C until the battery voltage reached 4.2V under a temperature environment of 25°C, and then charged at a constant voltage of 4.2V until the current value reached 0.05C. The charged test unit was disassembled, the negative electrode was taken out, and the thickness of the negative electrode after charging was measured with a micrometer. Then, the negative electrode expansion rate was calculated by the following formula, and the results are summarized in Table 1. Negative electrode expansion rate (%) = (negative electrode thickness after charging / negative electrode thickness during negative electrode production) × 100

[0088] Table 1

[0089]

[0090] As shown in Table 1, the expansion rates of the negative electrodes of Examples 1 to 3 are all less than 125%. On the other hand, the expansion rates of the negative electrodes of Comparative Examples 1 to 3 are greater than 125%. That is, in a negative electrode mixture layer having a negative electrode active material including a carbon material and a Si-based material and a binder, the pore size distribution measured by mercury penetration has two peaks R1 and R2, the peak R1 is greater than 0.5 μm and less than 1.5 μm, and the peak R2 is greater than 2 μm and less than 10 μm, and the content of the binder is greater than 4 mass % relative to the total mass of the negative electrode active material. By using such a negative electrode, the expansion of the negative electrode can be suppressed.

[0091] [Note]

[0092] (1) A negative electrode for a secondary battery, comprising a negative electrode collector and a negative electrode mixture layer arranged on the negative electrode collector, the negative electrode mixture layer having a negative electrode active material comprising a carbon material and a Si-based material and a binder, the pore size distribution of the negative electrode mixture layer measured by mercury penetration has two peaks R1 and R2, the peak R1 is greater than or equal to 0.5 μm and less than or equal to 1.5 μm, and the peak R2 is greater than or equal to 2 μm and less than or equal to 10 μm, and the content of the binder contained in the negative electrode mixture layer is greater than or equal to 4% by mass relative to the total mass of the negative electrode active material.

[0093] (2) The secondary battery negative electrode according to (1) above, wherein the average particle size of the Si-based material is 4 μm or more.

[0094] (3) The secondary battery negative electrode according to (1) or (2) above, wherein the content of the Si-based material is 30% by mass or more relative to the total mass of the negative electrode active material.

[0095] (4) The secondary battery negative electrode according to any one of (1) to (3) above, wherein the Si-based material includes a Si compound having a silicate phase and Si particles dispersed in the silicate phase.

[0096] (5) The secondary battery negative electrode according to any one of (1) to (4) above, wherein the Si-based material includes a Si compound having a carbon phase and Si particles dispersed in the carbon phase.

[0097] (6) The secondary battery negative electrode according to any one of (1) to (5) above, wherein a content of the Si-based material is 30% by mass or more and 60% by mass or less relative to the total mass of the negative electrode active material.

[0098] (7) The secondary battery negative electrode according to any one of (1) to (6) above, wherein the Si-based material has an average particle size of 4 μm or more and 12 μm or less.

[0099] (8) The secondary battery negative electrode according to any one of (1) to (7) above, wherein the carbon material contains graphite.

[0100] (9) The secondary battery negative electrode according to any one of (1) to (8) above, wherein the average particle size of the carbon material is 10 μm or more and 25 μm or less.

[0101] (10) A secondary battery comprising the secondary battery negative electrode according to any one of (1) to (9) above.

[0102] (11) A method for manufacturing a negative electrode for a secondary battery, comprising a first step and a second step, wherein in the first step, a negative electrode paste containing a negative electrode active material, a binder and a pore-forming material is applied to a negative electrode collector to form a coating, and then the coating is rolled, wherein the negative electrode active material contains a carbon material and a Si-based material, and in the second step, after the first step, the coating is heat-treated to decompose and gasify the pore-forming material to form a negative electrode mixture layer, wherein the pore size distribution of the negative electrode mixture layer measured by mercury penetration has two peaks R1 and R2, wherein the peak R1 is greater than 0.5 μm and less than 1.5 μm, and the peak R2 is greater than 2 μm and less than 10 μm, and the content of the binder contained in the negative electrode mixture layer is greater than 4% by mass relative to the total mass of the negative electrode active material.

[0103] Description of Reference Numerals

[0104] 10 secondary battery, 11 positive electrode, 12 negative electrode, 13 separator, 14 electrode body, 15 battery case, 16 case body, 17 sealing body, 18 insulating plate, 18, 19 insulating plates, 20 positive electrode lead, 21 negative electrode lead, 22 extension part, 23 filter, 24 lower valve body, 25 insulating member, 26 upper valve body, 27 cover, 28 gasket.

Claims

1. A negative electrode for a secondary battery, comprising a negative electrode current collector and a negative electrode mixture layer disposed on the negative electrode current collector, The negative electrode mixture layer comprises a negative electrode active material including a carbon material and a Si-based material, and a binder. The pore size distribution of the negative electrode mixture layer measured by mercury penetration has two peaks, R1 and R2. The peak value R1 is greater than or equal to 0.5 μm and less than or equal to 1.5 μm, and the peak value R2 is greater than or equal to 2 μm and less than or equal to 10 μm. The content of the binder contained in the negative electrode mixture layer is 4% by mass or more relative to the total mass of the negative electrode active material.

2. The negative electrode for a secondary battery according to claim 1, The average particle size of the Si-based material is 4 μm or more.

3. The negative electrode for a secondary battery according to claim 1 or 2, The content of the Si-based material is 30 mass % or more relative to the total mass of the negative electrode active material.

4. The negative electrode for a secondary battery according to claim 1 or 2, The Si-based material includes a Si compound having a silicate phase and Si particles dispersed in the silicate phase.

5. The negative electrode for a secondary battery according to claim 1 or 2, The Si-based material includes a Si compound having a carbon phase and Si particles dispersed in the carbon phase.

6. The negative electrode for a secondary battery according to claim 1 or 2, The content of the Si-based material is 30 mass % or more and 60 mass % or less relative to the total mass of the negative electrode active material.

7. The negative electrode for a secondary battery according to claim 1 or 2, The Si-based material has an average particle size of 4 μm or more and 12 μm or less.

8. The negative electrode for a secondary battery according to claim 1 or 2, The carbon material includes graphite.

9. The negative electrode for a secondary battery according to claim 1 or 2, The average particle size of the carbon material is 10 μm or more and 25 μm or less. 10 . A secondary battery comprising the negative electrode for a secondary battery according to claim 1 or 2.

11. A method for manufacturing a negative electrode for a secondary battery, comprising a first step and a second step, In the first step, after applying a negative electrode paste containing a negative electrode active material, a binder and a pore-forming material to a negative electrode current collector to form a coating film, the coating film is rolled, wherein the negative electrode active material contains a carbon material and a Si-based material. In the second step, after the first step, the coating film is subjected to a heat treatment to decompose and gasify the pore-forming material to form a negative electrode mixture layer. The pore size distribution of the negative electrode mixture layer measured by mercury penetration has two peaks, R1 and R2. The peak value R1 is greater than or equal to 0.5 μm and less than or equal to 1.5 μm, and the peak value R2 is greater than or equal to 2 μm and less than or equal to 10 μm. The content of the binder contained in the negative electrode mixture layer is 4% by mass or more relative to the total mass of the negative electrode active material.

Citation Information

Patent Citations

  • Negative electrode active material for lithium ion secondary battery, negative electrode mixture for lithium ion secondary battery, negative electrode for lithium ion secondary battery, and lithium ion secondary battery

    JP2013219059A